A melanoma cell state distinction influences sensitivity to MAPK pathway inhibitors - Konieczkowski, David J. (2014)
Most melanomas harbor oncogenic BRAF(V600) mutations, which constitutively activate the MAP kinase (MAPK) pathway. Although MAPK pathway inhibitors show clinical benefit in BRAF(V600)-mutant melanoma, it remains incompletely understood why 10-20% of patients fail to respond. Here, we show that RAF inhibitor sensitive and resistant BRAF(V600)-mutant melanomas display distinct transcriptional profiles. Whereas most drug-sensitive cell lines and patient biopsies showed high expression and activity of the melanocytic lineage transcription factor MITF, intrinsically resistant cell lines and biopsies displayed low MITF expression but higher levels of NF-κB signaling and the receptor tyrosine kinase AXL. In vitro, these MITF-low/NF-κB-high melanomas were resistant to inhibition of RAF and MEK, singly or in combination, and ERK. Moreover, in cell lines, NF-κB activation antagonized MITF expression and induced both resistance marker genes and drug resistance. Thus, distinct cell states characterized by MITF or NF-κB activity may influence intrinsic resistance to MAPK pathway inhibitors in BRAF(V600)-mutant melanoma.